تطور طرق تقوية الجوائز البيتونية المسلحة لمقاومة الانعطاف باستخدام مركبات FRP - غالية, رامية (Latakia University Journal -Engineering Sciences Series, 2018)
beams are subjected to effect of flexural and shear strength, and as the reinforced concrete beams are one of the most important structural elements, so care must be taken to treat any cracks that appear, whether vertical cracks resulting from the flexural or inclined cracks resulting from the shear. Recently many researches have been done to strengthen concrete beams to avoid flexural or shear strength by using FRP fiber reinforced polymer sheets and laminates: Carbon fiber reinforced polymer CFRP, Glass fiber reinforced polymer GFRP, Or Aramid fiber reinforced polymer AFRP. Current research present a proposition of conventional methods to strengthen concrete beams for flexural, and using materials of fiber reinforced polymer by using Different methods such as NSM method or EBR method, and the best method to provide the best contribution to improve resistance, which helps to develop the use of FRP in the reinforcement field. تتعرض الجوائز لتأثير عزوم انعطاف مترافقة مع قوى قص, وباعتبار الجوائز البيتونية المسلحة من أهم العناصر الإنشائية, لذلك يجب الاهتمام بمعالجة أي تشققات تظهر بها سواء كانت تشققات عمودية ناتجة عن الانعطاف أو مائلة ناتجة عن القص. أجريت في الآونة الأخيرة دراسات متعددة لتقوية الجوائز البيتونية على الانعطاف أو القص باستخدام شرائح أو صفائح بوليميرية مسلحة بالألياف (Fiber reinforced polymer FRP): الكربونيةCFRP , الزجاجية GFRP, الأراميدية AFRP . يقدم بحثنا الحالي عرضاً لبعض الطرق التقليدية لتقوية الجوائز على الانعطاف, واستخدام المواد البوليميرية المسلحة بألياف, باستخدام تقنيات مختلفة, هي تقنية NSM وتقنية EBR والطريقة الأفضل التي تقدم أفضل مساهمة في تحسين المقاومة, مما يساعد في تطوير استخدام FRP في مجال التقوية.